The Structure of Bivalvian Community in The Coast of Elak Elak Beach, West Sekotong, West Lombok, West Nusa Tenggara As An Enrichment of Invertebrate Animal Material for Senior High School Students - Inda Wahyuni; Didik Santoso; I Putu Artayasa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Elak elak beach has a sea and a coast with a substrate texture that is very suitable as a habitat for Mollusca including bivalves. Bivalves have many roles for the environment, especially in providing food for various other species in the food chain and can be used to determine water quality. This study aims to determine the community structure and distribution pattern of bivalves in Elak Elak Beach and to see student responses to booklets. The method used in this research is the line transect and quadratic method. The results of the study of the bivalves class molluscs found in the Elak Elak Coastal Coast consisted of 11 species belonging to 7 families. The species consists of Anadara gubernaculum, Anadara granosa, Gafrarium dispar, Glycymeris pectunculus, Liconcha ornata, Lucinoma heroica, Mactra grandis, Mactra nitida, Mactra ornata, Donax faba and Trachycardium flavum. The relative abundance reaches 40% where the highest abundance of bivalves is species Mactra grandis with a relative abundance value of 39.39%. The categories of diversity (H') are medium and uniformity (E) is high, and inversely proportional to the dominance value (C) is low. The structure of the bivalves community based on abundance, diversity, uniformity and dominance that has been studied shows the condition of the West Sekotong Elak Elak Beach, West Lombok district, it can be concluded that the community structure is still in normal condition. The distribution pattern of Bivalves on Elak Elak Beach, West Sekotong is divided into 2 types, namely there are uniform and clustered which are seen based on the calculated value of the Morisita dispersion index. Students' responses to booklets are that students respond very well and students are also very positive in responding to booklets as material enrichment about invertebrate animals for senior high school students.